2014
DOI: 10.1177/1708538114522227
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between complete blood count parameters and Fontaine’s Stages in patients with peripheral arterial disease

Abstract: Both red blood cell distribution width and mean platelet volume are found to be associated with the severity of atherosclerotic disease in patients with peripheral arterial disease. This finding hypothesizes that complete blood counting parameters may serve as a beneficial and cost-effective method for monitoring atherosclerotic peripheral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…Zalawadiya et al measured RDW in 6,950 participants from general population and after adjustment for potential confounders they showed that, there is a direct relationship between RDW and prevalence of PAD . Demirtas et al studied 82 PAD patients and showed that RDW increased incrementally with the progression of PAD severity stages …”
Section: Role Of Rdw In Peripheral Artery Disease and Rdwmentioning
confidence: 99%
See 1 more Smart Citation
“…Zalawadiya et al measured RDW in 6,950 participants from general population and after adjustment for potential confounders they showed that, there is a direct relationship between RDW and prevalence of PAD . Demirtas et al studied 82 PAD patients and showed that RDW increased incrementally with the progression of PAD severity stages …”
Section: Role Of Rdw In Peripheral Artery Disease and Rdwmentioning
confidence: 99%
“…46 Demirtas et al studied 82 PAD patients and showed that RDW increased incrementally with the progression of PAD severity stages. 47…”
Section: Role Of Rdw In Peripheral Artery Disease and Rdwmentioning
confidence: 99%
“…Increased MPV has been reported to correlate with intracoronary thrombus burden in the IRA before mechanical reperfusion, in-hospital major adverse cardiovascular events in patients with STEMI undergoing PCI [7,8], and 1-year incidence of death or myocardial infarction in patients with acute coronary syndrome undergoing PCI [9]. Furthermore, recent studies by Demirtas et al [10] and Yavuz et al [11] showed there is an interaction between MPV and disease severity in many types of arterial-occlusive diseases, such as peripheral artery disease and thromboangiitis obliterans. However, the association between MPV and myocardial reperfusion in patients with STEMI and successful epicardial reperfusion after PCI has not been fully investigated.…”
Section: Introductionmentioning
confidence: 96%
“…A prospective study by Kullar et al [42] reviewed the relationship between post-operative NLR values and graft failure that can develop afterwards and postoperative high NLR values were found to be associated with graft failure. Another study by Demirtaş et al [43] prospectively reviewed 50 patients with the diagnosis of new peripheral arterial occlusion. In this study preoperatively taken complete blood count parameters were examined according to Fontaine's classification.…”
Section: Discussionmentioning
confidence: 99%